“BYSTANDER EFFECT” IN CASES OF CORRUPTION IN CORPORATE, BUREAUCRATIC AND POLITICAL ORDERS - Vera Astuti; Ratna Candra Sari (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2019)
E-KTP Corruption is an organized crime that occurs in Indonesia. The corruption that has been established is to form an organized network due to the phenomenon